Integrasi Konsep Ta’dib dengan Program 5S dalam Pembentukan Karakter Sosial dan Cinta Damai Siswa - Ilyasa, Faisal Fauzan; Permana, Rizal; Jalal, Muhammad Rifky Faisal; Fazar, Fahmi; Syahidin, Syahidin (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to integrate the concept of ta'dib, which emphasizes the formation of manners, morals, and ethics as proposed by Syed Naquib al-Attas, with the 5S program (Smile, Greeting, Greeting, Polite, Courteous) in the context of character education at SMK ICB Cinta Niaga. A qualitative approach with a case study design was used to explore the implementation of this program and its impact on student character building. Data were collected through interviews, observations, and document analysis, then analyzed using NVivo12 software. The results show that ta'dib values in the 5S program can enhance various aspects of students' character development, particularly in improving students' social interactions (such as mutual respect and cooperation among peers), fostering harmonious teacher-student relationships (through enhanced communication and mutual appreciation), and strengthening the habituation of positive behaviors (such as discipline, responsibility, and empathy). Ta'dib values are reflected in simple yet meaningful habits that support holistic character building in accordance with Islamic values. This finding confirms the relevance of ta'dib in modern education to answer the challenges of globalization. However, this study has limitations in the limited scope of the school, so the generalization of the results of this study is a challenge. Further research is recommended to expand the scope of locations and use a mixed-method approach to deepen the analysis and produce more comprehensive findings.